CONTRIBUTIONS OF INNOVATION TO FAMILY FARMING: A MULTICASE STUDY (REMUNOM, 2026)
Family farming has been playing an increasingly important role in the Brazilian economy. However, uncertainties and difficulties permeate this context, making innovation intrinsic to the search for creative solutions aimed at facing contemporary challenges. Thus, the research aimed to analyze how innovation contributes to the economic development of family farms in the Vale do Caí Region/RS. To this end, a multi-case study was used with three rural properties, whose data were collected through in-depth individual interviews with family farmers, document analysis and direct non-participant observation. The results made it possible to identify the contribution of innovation on the properties in the scope of maximizing revenue, continuous production with inventory management, adoption of operational practices oriented towards sustainability, managerial efficiency and the stages of the constant innovation cycle, which provide new demands to the rural business.